1990
DOI: 10.1007/bf01188403
|View full text |Cite
|
Sign up to set email alerts
|

Acute neuropathological changes in the caudate nucleus caused by MPTP and methamphetamine: Immunohistochemical studies

Abstract: Three days after the administration of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) or methamphetamine to mice, there is degeneration and disappearance of punctate tyrosine hydroxylase-containing synaptic endings in the caudate nucleus. The neuropil is occupied with longer, varicose, branching fibres, which appear to be preterminal fibres. An intense gliosis occurs. The sparsely-occurring glial cells, with profuse lightly-stained (by glial fibrillary acidic protein) processes which are primarily located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…Immunohistochemical examination reveals that MA reduces TH-IR in the striatum and other dopaminergic terminal fields in the forebrain (Hess et al, 1990;Pu and Vorhees, 1993;Pu et al, 1994;Trulson et al, 1985). Furthermore, astrogliosis and argyrophilia, indices of neuronal damage, are present in areas corresponding to the loss of TH-IR after MA treatment, thereby supporting the conclusion that MA injures dopaminergic terminals (Bowyer et al, 1994;Hess et al, 1990;Miller and O'Callaghan, 1994;O'Callaghan and Miller, 1994;Pu and Vorhees, 1993;Pu et al, 1994;Ricaurte et al, 1982).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Immunohistochemical examination reveals that MA reduces TH-IR in the striatum and other dopaminergic terminal fields in the forebrain (Hess et al, 1990;Pu and Vorhees, 1993;Pu et al, 1994;Trulson et al, 1985). Furthermore, astrogliosis and argyrophilia, indices of neuronal damage, are present in areas corresponding to the loss of TH-IR after MA treatment, thereby supporting the conclusion that MA injures dopaminergic terminals (Bowyer et al, 1994;Hess et al, 1990;Miller and O'Callaghan, 1994;O'Callaghan and Miller, 1994;Pu and Vorhees, 1993;Pu et al, 1994;Ricaurte et al, 1982).…”
Section: Introductionmentioning
confidence: 84%
“…Administration of this compound to experimental animals results in a reproducible profile of neurotoxicity that consists of persistent reductions in striatal dopamine content, loss of TH activity, and diminished numbers of dopamine reuptake sites (Bowyer et al, 1994;Hotchkiss and Gibb, 1980;O'Callaghan and Miller, 1994;Ricaurte et al, 1980;Seiden et al, 1976;Wagner et al, 1980). Immunohistochemical examination reveals that MA reduces TH-IR in the striatum and other dopaminergic terminal fields in the forebrain (Hess et al, 1990;Pu and Vorhees, 1993;Pu et al, 1994;Trulson et al, 1985). Furthermore, astrogliosis and argyrophilia, indices of neuronal damage, are present in areas corresponding to the loss of TH-IR after MA treatment, thereby supporting the conclusion that MA injures dopaminergic terminals (Bowyer et al, 1994;Hess et al, 1990;Miller and O'Callaghan, 1994;O'Callaghan and Miller, 1994;Pu and Vorhees, 1993;Pu et al, 1994;Ricaurte et al, 1982).…”
Section: Introductionmentioning
confidence: 95%
“…In rodents, methamphetamine administration has been shown to increase glial cells (Hess et al 1990;Pu and Vorhees 1993), and the increased levels of Cho are found in glial cells (Urenjak et al 1993). Therefore, the decrease in CrϩPCr/Cho could be accounted by the elevated Cho level in methamphetamine users.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, METH administration indeed has been associated with reduced glial glutamate uptake and / or recycling (Yamamoto and Bankson, 2005). Additionally, METH causes activation of glial cells (Hess et al, 1990;Pu and Vorhees, 1993), specifically microglia (Asanuma et al, 2003;Escubedo et al, 1998), which in turn may lead to inhibition of glutamate uptake (Zou and Crews, 2005) and glutamine synthesis (Muscoli et al, 2005). Inhibition of glial glutamate recycling also might increase extracellular glutamate and therefore lead to excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%